The Analysis of Risk Factors for Periprosthetic Joint Infection in Indian Hospital Settings - Madhav Madhusudan Singh; Munish Sood; Akshay Kumar Sharma; Manish Parsad; Saurabh Mahajan; Kamparsh Thakur (GAIMS Journal of Medical Sciences, 2024)
Background: Periprosthetic Joint Infection (PJI) is a nightmare for both patient and surgeon. Despite advances made in arthroplasty still incidence is 1-2%. Many of our understanding regarding PJI come from registry data. Despite performing large number of joint replacement surgeries there is a lack of optimal registry data from this part of world. We retrospectively analysed PJI data in four NABH accredited hospital of around 5370 patients and tried to identify common risk factors in them and proposed a clinical scoring system for assessing risk of PJI.